Determinants of Transfer Pricing in Energy Sector Companies with Managerial Ownership as a Moderation - Auro Osti Berliana Hutabarat; Nella Yantiana; Muhammad Fahmi; Nina Febriana Dosinta; Syarif M Helmi (Poltanesa, 2025)
The purpose of this research is to analyze the effect of leverage and profitability on transfer pricing with manajerial ownership as the moderating variable. The population in this research were energy sector companies listed on the Indonesia Stock Exchange during the period 2019-2023. The sampling method used was purposive sampling, the overall sample used in this study was 175 annual financial report from 35 companies. The findings reveal profitability do not have a significant effect on transfer pricing, leverage and manajerial ownership  have a significant effect on transfer pricing, but manajerial ownership can not significantly moderate the relationship between profitability and transfer pricing